Fuzzy sliding mode controller for cascaded multilevel inverter - Shumran, Alshammari Fahad (2015)
This research provide an analytical study to sliding mode controller and fuzzy sliding mode controller for cascaded 5-Level inverter. The cascaded 5-Level inverter used in this research is implemented based on phase shifted Pulse width modulation technique. An output LC filter is used to reduce harmonics elements. The system is implemented mathematically using a state space representation. Then the averaging model is obtained on order to prepare the system’s equations to be appreciated with sliding mode method. After modeling the system, sliding mode controller is designed. Lastly, Fuzzy logic controller is designed with desired scaling factor to fuzzify the sliding surface. Both controller are connected to three types of load to identify their behavior. The simulation results show that the proposed fuzzy sliding mode controller is more robust than sliding mode controller.